Co-infection of Malassezia sympodialis With Bacterial Pathobionts Pseudomonas aeruginosa or Staphylococcus aureus Leads to Distinct Sinonasal Inflammatory Responses in a Murine Acute Sinusitis Model - Lee, Keehoon; Zhang, Irene; Kyman, Shari; Kask, Oliver; Cope, Emily Kathryn (Frontiers in Cellular and Infection Microbiology, 2020)
The host-associated microbiota has demonstrated its importance to human health. In the airways, the composition and diversity of the mucosal microbial communities of patients are related to their airway health status. However, the relationship between airway microbiota and respiratory inflammation is not well understood. Chronic rhinosinusitis (CRS) affects up to 14% of the US population. Previous studies show decreased microbial diversity in CRS patients and enrichment of either Staphylococcus aureus or Pseudomonas aeruginosa. Although bacterial community composition is variable across CRS patients, Malassezia is a dominant fungal genus in the upper airways of the majority of healthy and CRS subjects. We hypothesize that distinct bacterial-fungal interactions differentially influence host mucosal immune response. Thus, we investigated in-vitro and in-vivo interactions between Malassezia sympodialis, P. aeruginosa, and S. aureus. The in-vitro interactions were evaluated using the modified Kirby-Bauer Assay, Crystal Violet assay for biofilm, and FISH. Murine models of acute sinusitis were used to investigate relationships with the host immune response. S. aureus and P. aeruginosa were intranasally instilled in the presence or absence of M. sympodialis. Changes in the microbiota were determined using 16S rRNA gene sequencing and host immune response was measured using quantitative real-time PCR (qRT-PCR). In vitro, only late stage planktonic P. aeruginosa and its biofilms inhibited M. sympodialis. Co-infection of mice with M. sympodialis and P. aeruginosa or S. aureus differently influenced the immune response. In co-infected mice, we demonstrate different expression of fungal sensing (Dectin-1), allergic responses (IL-5, and IL-13) and inflammation (IL-10, and IL-17) in murine sinus depending on the bacterial species that co-infected with M. sympodialis (p<0.05). The results show the species-specific interactions in airway-associated microbiota and these may be implicated in some subsets of CRS disease. The understanding of the role of bacterial-fungal interactions in CRS will contribute to development of novel therapies toward manipulation of the airway microbiota